Model of health information sharing behavior among patients in cervical cancer - atmi, Ragil Tri (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
Cervical cancer is the second highest cause of death for women in Indonesia, despite a deadly illness, patients with cervical cancer are not desperate to survive. Instead, they are motivated to undertake positive actions, one of which is to do health informtion sharing or share information on environmental health tersekatnya. This study aims to look at how the patterns of behavior of sharing health information on cervical cancer patients, as well as the motive behind their actions the health information sharing. This study uses the method of qualitative research grounded approach. Location of the study conducted in Surabaya, while the search for informants researchers used snowball sampling. The results from this study is there are different behavior patterns of health information sharing among cervical cancer patients who have been diagnosed with advanced cervical cancer with cervical cancer at an early stage level.